Development of a Novel Methodology to Retrofit Legacy Systems in the Context of Industry 4.0 - Rafael Da Silva Mendonca; Marenice Melo De Carvalho; Guido Soprano Machado; Claudia Sabrina Monteiro Da Silva; Renan Landau Paiva De Medeiros; Vicente Ferreira De Lucena (IEEE Access, 2023)
This research aims to develop a comprehensive methodology for retrofitting legacy industrial automation systems, encompassing hardware and software updates, testing, and validations, to ensure that the system aligns with current and future needs. The proposed methodology not only addresses technical aspects but also considers the integration of emerging technologies such as the Internet of Things (IoT), cyber-physical systems, cloud computing, and digital twins. The main goal of the retrofitting process is to enhance the efficiency, integration, security, and interoperability of the legacy system, enabling it to remain competitive in the long term. Legacy systems may require retrofitting for various reasons, including incompatibility with new devices or technologies, inability to meet the current needs of the manufacturing process, vulnerability to security threats, or noncompliance with current industry standards and regulations. Through the proposed methodology, step-by-step guidance will be provided, enabling organizations to successfully update their legacy systems using retrofitting techniques and capitalize on the advantages offered by Industry 4.0.